EXPLOITATION OF IRVINGIA WOMBOLU (OGBONO) BY RURAL WOMEN IN ETSAKO CENTRAL LOCAL GOVERNMENT AREA OF EDO STATE - Alawiye, Mahmud A.; Akemien, N. N.; Adaaja, B. O.; Ayuba-Abdul, J. M.; Owoeye, E. A.; Zaman, E. Y. (FUDMA JOURNAL OF SCIENCES, 2024)
Exploitation of Irvingia wombolu constitutes a good source of livelihood and earnings for women in local communities. The study assessed rural women involvements in the exploitation of Irvingia wombolu popularly known as Ogbono in Etsako central local government area of Edo state, Nigeria. The study employed multi-stage random sampling and analyzed the data collected from 120 sampled respondents using SPSS to generate the descriptive statistics and principal component analysis (factor analysis) in line with the study objectives. The results showed that majority (53.3%) are within their active age group of 31-40years. Majority (63.3%) of the sampled respondents were married. Majority of them had not more than 5 household size members. Most of them earn average of NGN30,000 – NGN40,000 monthly from Irvingia wombolu exploitation. Similarly, majority of them were into Irvingia wombolu business as their main occupation on forest land size of between 2-4 acres and farming experience of 10 years or below. In addition, homestead garden was mostly used (70.8%) for the cultivation of Irvingia wombolu tree by the respondents in the study area. Also, quite a number of them asserted that the exploitation of Irvingia wombolu had increased their earnings and benefitted their households’ needs. However, the respondents noted that they had major challenge of inadequate finance for their business. Lastly, spoilage due to poor storage was a major factor (-0.778) limiting their involvement in exploitation of Irvingia wombolu in the study area. On this note, priority should be given to investment in storage facilities in order to...
Keywords: Irvingia wombolu; Rural women; Exploitation; Perceived benefits